Produksi Asi Pada Ibu Postpartum Dengan Pendekatan Etnomedisin Daun Torbangun Di Klinik Surya Medika Way Halim Bandar Lampung - Septi Ristiyana; Margareta Rinjani; Anisa Rina (Jurnal Ilmu Kebidanan, 2023)
Background: In the physiological state of breastfeeding, the nutritional needs of mothers ncrease because the need for milk to produce breast milk, one of the efforts that can be made to ncrease the rate of excretion and production of breast milk s through the use of traditional medicinal herbs, there are several plants that we believe are good, gradually decrease or have been proven tested. Scientifically increasing the quality and quantity of ASI, for example the foliate plant (Coleus amboinicius) (Ministry of Health, 2016). The formulation of the problem in this research is "Is there an effectiveness of torbangun daun on ncreasing the production of ASI in postnatal mothers at the surya medika clinic in Bandar Lampung. The aim is to find out the effectiveness of torbangun daun on ncreasing ASI production in postpartum mothers. Methods: This research uses the type of Quantitative research with the Simple Experiment Design (Posttest Only Control Group Design). The overall population of post-partum mothers at the Surya Medika Way Halim Bandar Lampung Clinic is a total of 28 people. Results: The mean ASI production rank in the control group, namely 8.96, is lower than the mean ASI production Rank in the ntervention group 20.04. P value was found to be 0.001 (